Redefining the public sphere on the shifting boundaries of journalism: A netnography of community deliberation on facebook about Potchefstroom - Gouws, Andries Jacobus (Stellenbosch : Stellenbosch University, 2025)
Thesis (DPhil)--Stellenbosch University, 2025.